Pengembangan Sistem Pendukung Keputusan Berbasis Web untuk Diagnosis Anemia dengan Metode Certainty Factor - Nurwegiono, Muhammad; Zen, Bita Parga (Jurnal Ilmiah Media Sisfo, 2025)
Adolescent girls are a vulnerable group prone to anemia due to increased iron requirements during puberty. Undiagnosed anemia can negatively impact health, productivity, and academic performance. This study aims to design and develop a web-based Decision Support System (DSS) to assist in diagnosing various types of anemia based on symptoms experienced by users, using the Certainty Factor (CF) method. The system was developed using the Waterfall model, which includes requirement analysis, system design, coding, and testing through the blackbox method. System testing was conducted among adolescent girls in the Sumber Sekar area and showed that all main features of the system functioned properly, with a functional accuracy rate of approximately 95% in blackbox testing. The system is also considered user-friendly and capable of providing early diagnostic insights and recommendations efficiently and accurately. It is expected to serve as an initial support tool to raise awareness and facilitate early detection of anemia, particularly among adolescent girls.